IMPULSIVE DIFFUSION EQUATION ON TIME SCALES - Gulsen, Tuba; Sian, Shaida Saber Mawlood; Yilmaz, Emrah; Koyunbakan, Hikmet (Etamaths Publ, 2018)
Application of boundary value problems (BVP's) on an arbitrary time scale T is a fairly new and important subject in mathematics. In this study, we deal with an eigenvalue problem for impulsive diffusion equation with boundary conditions on T. We generalize some noteworthy results about spectral theory of classical diffusion equation into T. Also, some eigenfunction estimates of the impulsive diffusion eigenvalue problem are established on T.
Keywords: time scales; impulsive diffusion equation; spectral theory